We Only Come Here to Struggle : Stories from Berida's Life - Ndambuki, Berida, 1936-; Robertson, Claire C., 1944- (Book collections on Project MUSE., 2000)
Here is the life history of Berida Ndambuki, a Kenyan woman trader born in 1936, who speaks movingly of her experiences under the turbulences of late British colonialism and independence. A poverty survivor, Berida overcame patriarchal constraints to reclaim the rights to her labor, her body, and her spirit. She invokes a many-faceted picture of central Kenyan life in this compelling narrative.